Sustainable production of cement masonry blocks with the combined use of ﬂy ash and quarry waste - Sathiparan, N.; Jaasim, J.H.M.; Banujan, B. (Elsevier, 2022)
Cement-sand block is a primary construction material used for masonry house units. River sand and cement are the two main ingredients in cement block construction; however, cement is notoriously unfriendly to the environment due to excessive energy consumption during cement manufacture and considerable CO and other greenhouse gas emissions. Overusing river sand has several adverse eﬀects on the environment and society, including a deepening of the riverbed, a decline in the water table, and the extinction of freshwater aquatic life. Therefore, ﬁnding substitutes for cement and river sand has received much attention in recent years. It would be beneﬁcial to use ﬂy ash and quarry refuse for making masonry blocks since it would use less energy and cause less environmental damage. The present study emphasizes the combined use of quarry waste (100% substitute for river sand) and ﬂy ash (0, 10, 20, 30 and 40% substitute for cement) for sustainable masonry block production. The physical, mechanical, and durability properties of cement blocks made using ﬂy ash and quarry waste underwent a thorough investigation. Results showed that, even though the compressive strength and impact strength of masonry blocks decreased with ﬂy ash content, the strength of masonry blocks with quarry waste and 40% ﬂy ash was higher than that of conventional masonry blocks. The substitution of ﬂy ash for cement potentially increased the alkaline and acid resistance and also improved the thermal performance. Also, the replacement of ﬂy ash for cement in the masonry blocks signiﬁcantly reduced the total cost, embodied energy and CO2 emission. It can be inferred from the study that using quarry waste as a full river sand substitute and ﬂy ash as a partial cement substitute in masonry blocks is a cost-eﬀective and sustainable method
Keywords: Masonry block; Fly as; River sand; Quarry waste; Sustainable